Digital Financial Capability Towards Improving Entrepreneurial’s Business Performance - Nor, Nainatul Farzuha; Saaidun, Noor Saidatul Natrah; Mohamad, Noorkartina (Journal of Accounting, Business and Management (JABM), 2024)
Digital financial, play a vital role for the country growth, provides the prospects for encouraging economic development during the looming economic downturn. Entrepreneurs play a significant role in economic growth and development. Today, digital financial become a large portion among entrepreneurship to increase their business performance. The objectives of this research to study the capability of financial digitalization towards entrepreneurial business. Therefore, on the base of previous literature, we developed hypothesis digital financial, and data collected through structured questionnaires among entrepreneurs. The findings of this research endeavour to shed light on developing and popularizing digital financing by providing services which are cheap, secure, and low risk from a supply-side perspective, as well as adopting and adjusting digital financing by enhancing financial literacy, which would be necessary from the demand-side perspective. Therefore, to facilitate entrepreneurial success and improvement in entrepreneurial industry, it is important to provide entrepreneurs with financial education. Meanwhile, improvements to the financial environment should also be considered.